Respuesta :
I would simplify each equation and then plug in 6 for x.
A.) [tex]\frac{2}{3}x-2= \frac{1}{3} x[/tex] Subtract 2/3x on both sides
[tex]\frac{2}{3}x-2- \frac{2}{3}x= \frac{1}{3}x-\frac{2}{3}x[/tex]
[tex]-2=-\frac{1}{3}x[/tex] Now you plug in 6
[tex]-2=-\frac{1}{3} (6)[/tex]
[tex]-2 = -\frac{6}{3}[/tex]
-2 = -2
x = 6 is the solution for choice A
Short Answer
It's A
Solution
A
2/3 x - 2 = 1/3 x Subtract 2/3x from both sides
2/3x - 2/3x - 2 = 1/3x - 2/3 x Combine like terms
- 2 = - 1/3 x Multiply both sides by - 3
- 2 * - 3 = 3 * - 1/3 x
- 6 = - x Multiply by -1
x = 6
B
B looks like the same thing, but the 2 is a plus 2. When you solve for x you go through exactly the same steps. Your answer becomes - 6
C
C adds 2/3 x to both sides. The result is x = - 2
D same as C only x = 2